Efecto de cinco niveles de goma de tara sobre el comportamiento productivo, mineralización ósea y morfometría intestinal en pollos de carne - Zea M., Otto (2019)
The aim of this study was to determine the effect of five levels of tara gum on productive performance, bone mineralization, glucose and cholesterol levels, and intestinal morphometry in broilers from 1 to 21 days of age. A total of 200 male BB cobs of the Cobb500 line were used, distributed in five treatments with four repetitions and 10 animals per repetition: T1, basal diet without tara gum (control); T2, T3, T4 and T5, basal diet with tara gum (0.05, 0.10, 0.15 and 0.20% respectively). All diets contained 3072 kcal ME/kg and 20.5% crude protein. The feed meal and water were offered ad libitum. The data were analyzed under a completely randomized design using the ANOVA procedure and the Duncan test for comparison of means. The results showed that body weight and body-weight gain were better in T3 than in T4 and T5 (p<0.05), both in the second and in the third week of age. Also, tara gum influenced the depth of the crypt and the height of the villus and crypt in the jejunum compared to the control group. No statistical difference was found in indicators of bone mineralization, cholesterol or glucose levels. It is concluded that the addition of 0.1% tara gum favors body weight, body-weight gain and intestinal morphology in broilers.